(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article is devoted to periphrases, which are one of the interesting and complex phenomena of linguistics. Periphrases belong to the category of tropes – stable combinations of artistic speech used semantically indivisibly and everywhere. The article discusses the features of semantics and grammatical design of descriptive phrases – periphrases. Attention is focused on the fact that the use of substantive periphrases helps to expand the vocabulary and enrich the language with new expressions.